Comprehensive Characterization of Immune Landscape Based on Epithelial-Mesenchymal Transition Signature in OSCC: Implication for Prognosis and Immunotherapy - Zhang, Si-yuan; Ren, Xian-yue; Wang, Chun-yang; Chen, Xi-juan; Cao, Ruo-yan; Liu, Qin; Pan, Xue; Zhou, Jia-ying; Zhang, Wei-lin; Tang, Xin-Ran; Cheng, Bin; Wu, Tong (Frontiers in Oncology, 2021)
Current anatomic TNM stage classification fails to capture the immune heterogeneity of OSCC. Increasing evidences indicate a strong association between epithelial-mesenchymal transition (EMT) and tumour immune response. In this study, we employed the EMT signature to classify OSCC patients into epithelial- and mesenchymal- phenotypes using TCGA and GSE41613 transcriptome data. ESTIMATE and CIRBERSORT analysis implied that EMT signature was originated from stroma, and M-type tumours were characterized as “immune-hot” with more immune cells infiltration in contrast to E-type ones. The low active and high inactive immune cells infiltration, and high immune checkpoints expressions demonstrated an immunosuppressive characteristic of M-type tumours. Importantly, we developed and validated a novel prognostic classifier EIT based on EMT score, 7 immune checkpoints expressions and TNM stage, which could improve the prediction efficiency of current clinical parameter. Together, our findings provide a better understanding of the tumour immune heterogeneity and may aid guiding immunotherapy in OSCC.